1988
DOI: 10.1111/j.1471-0528.1988.tb06794.x
|View full text |Cite
|
Sign up to set email alerts
|

The variation in cervical hydroxyproline and cervical water with age

Abstract: Summary. The squamocolumnar junction is frequently not visible in the postmenopausal patient. This study attempts to identify some of the changes in the cervix that may account for this observation. Twentyfour cervical biopsy samples taken at the squamocolumnar junction were analysed for hydroxyproline (collagen) and water content. There was significantly more hydroxyproline (collagen) in the premenopausal woman than the postmenopausal woman. Similarly, there was higher percentage of water in the biopsies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…In agreement with Roberts et al [ 12 ] the present study indicates that cervical collagen concentration increases with age. As high collagen concentrations are associated with long duration of labor [ 13 ], this corresponds well to studies showing that dystocia is more common among older women [ 25 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with Roberts et al [ 12 ] the present study indicates that cervical collagen concentration increases with age. As high collagen concentrations are associated with long duration of labor [ 13 ], this corresponds well to studies showing that dystocia is more common among older women [ 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…In most connective tissues there will be a decrease in the amount of tissue due to an imbalance in matrix synthesis and breakdown [ 11 ]. It is suggested that cervical collagen concentration is increased with age whereas water content is decreased [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Briey, the postmenopausal HW Raman spectra showed increased lipids (2880 cm À1 ) [45][46][47] and proteins (2946 cm À1 ) 43,44 content, whereas an elevated tissue water content (3100-3700 cm À1 broad water band peaked at 3400 cm À1 ) was noticed in premenopausal women. 43 Within the postmenopausal women, the postmenopausal-prevagifem patients showed the most increased lipids and proteins content while the least water content. However, aer the Vagifem Ò therapy (postmenopausal-postvagifem), the lipids and proteins started to decrease and water began to increase towards premenopausal women.…”
Section: Discussionmentioning
confidence: 88%
“…1b) clearly reect the specic biomolecular changes in the cervical tissue HW Raman spectra associated with the menopausal status of women. For instance, the spectra measured from the cervix of postmenopausal-prevagifem women (atrophy) increased signicantly at 2880 and 2946 cm À1 , [43][44][45][46][47] whereas the converse was true for the water Raman signal (3400 cm À1 ) 43,44,48 compared to premenopausal women (unpaired Student's t-test ( p < 0.05)). However, aer the Vagifem treatment, postmenopausal women with severe atrophy (postmenopausal-prevagifem) move towards premenopausal women due to elevated levels of the female reproductive hormone estrogen in the cervix.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps labour is made more difficult by changes in the connective tissues and the collagen in the uterus and cervix. 33 Whereas from a cultural, economic and educational viewpoint there are great advantages in delaying first childbirth, from a biological standpoint increasing maternal age is a disadvantage.…”
Section: Changes In Human Ecologymentioning
confidence: 99%